Analysis of the Load Sharing Characteristic of Compound Planetary Gear Set Under the Common Impact of Internal and External Excitation - Chao Yang; Haibo Zhang; Huijuan Zhu; Liping Feng (Jixie chuandong)
Current researches on load sharing characteristic concentrate on fluctuation of load sharing under the condition of single factor changing， which results in a poor comprehension on the load sharing behavior under the condition of multi-factors changing together，that’s to say， it’s difficult to find the most essential excitation among multi-factors affecting load sharing behavior，to improve the load sharing characteristic efficiently. To solve this problem，a multiple-factor analysis model is built and incorporated with “translational-rotaional” dynamic model of compound planetary gear set to give load sharing coefficient under different confugurations. By using single to noise analysis， and the contribution of each control parameter on load sharing behavior is quantified. The results indicate that， the impact of internal excitations on load sharing behavior is much bigger than that of external excitations， increasing bearing clearance contributes to load sharing behavior， and decreasing the transmission error of central parts is the most efficient way to improve load sharing behavior.